2015
DOI: 10.1016/j.cbi.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary regional PBPK model of lung metabolism for improving species dependent descriptions of 1,3-butadiene and its metabolites

Abstract: 1,3-Butadiene (BD), a volatile organic chemical (VOC), is used in synthetic rubber production and other industrial processes. It is detectable at low levels in ambient air as well as in tobacco smoke and gasoline vapors. Inhalation exposures to high concentrations of BD have been associated with lung cancer in both humans and experimental animals, although differences in species sensitivity have been observed. Metabolically active lung cells such as Pulmonary Type I and Type II epithelial cells and club cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The blood volume ( V blood ) and cardiac output ( Q co ) of hamsters that were reported in the literature were used for the PBPK model development [ 22 , 23 ]. The blood flow rate for the trachea ( Q trachea ) was calculated by multiplying Q co by 2.1% [ 24 , 25 , 26 ]. The blood flow rate for the rest of the body ( Q rest ) was calculated by subtracting Q trachea from Q co .…”
Section: Methodsmentioning
confidence: 99%
“…The blood volume ( V blood ) and cardiac output ( Q co ) of hamsters that were reported in the literature were used for the PBPK model development [ 22 , 23 ]. The blood flow rate for the trachea ( Q trachea ) was calculated by multiplying Q co by 2.1% [ 24 , 25 , 26 ]. The blood flow rate for the rest of the body ( Q rest ) was calculated by subtracting Q trachea from Q co .…”
Section: Methodsmentioning
confidence: 99%
“…Some activities such as esterification of inhaled steroidal drugs are well-known examples of pulmonary metabolism (Miller-Larsson et al, 1998). In an interesting modelling approach for lung metabolism, Campbell et al (2015) developed a regional PBPK model for lung for 1,3-butadiene and its metabolites taking into account metabolic capabilities specific to sub-divided regions within lungs such as oral/nasal pathways, conducting airways (trachea, bronchi, and anterior bronchioles), transitional airways (terminal bronchioles), and the alveolar region. Results showed that inclusion of differential lung metabolism was important for explaining the observed species differences in the pulmonary metabolism of 1,3-butadiene.…”
Section: Non-absorptive Clearancementioning
confidence: 99%
“…Because of these difficulties, assessment of reactive metabolites is well suited to benefit from PBPK and PBPK/PD models which aim to describe the tissue exposure and potential toxicity of reactive metabolites in silico. Mathematical modeling for the predictive safety of reactive metabolites has been applied for years in the field of environmental toxicology, where such models allow studies to be simulated which would not be experimentally possible. , …”
Section: Systems Pharmacology Approaches For Reactive Metabolite Risk...mentioning
confidence: 99%
“…Mathematical modeling for the predictive safety of reactive metabolites has been applied for years in the field of environmental toxicology, where such models allow studies to be simulated which would not be experimentally possible. 321,322 Understanding the propensity for a compound to induce damage through the production of reactive metabolites involves understanding the exposure of the parent in metabolic tissues, the rate of conversion to reactive metabolite, accumulation of the reactive metabolite, and the formation of adducts with endogenous proteins and neutralization processes (e.g., GSH) (Figure 10). The ADME of the parent can be modeled utilizing standard PBPK models, with emphasis on the distribution to the primary metabolic tissues (e.g., liver, kidney) and the rate of metabolic conversion into the reactive metabolite.…”
Section: Systems Pharmacology Approaches For Reactive Metabolite Risk...mentioning
confidence: 99%